(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the bibliographic instruction – the textbook on syntax of the edition in 1914. The maintenance of the educational book in aspect of conformity of the linguistic theory of beginning XX century is critically stated. I. Nechuj-Levitskyi’s role during normalization of the Ukrainian language is underlined.